Diagnostic instruments of the current state of preventive nursing care for postpartum women with thromboembolism - Mercy Silva Martínez; Omayda Urbina Laza; Iván Parada Ferrera; Gustavo Galán Bermudes; Liuba González Espangler (Revista Habanera de Ciencias Médicas)
Introduction: Research instruments for diagnosing the current state of a process contribute to identifying the problems of health processes and the action plan.